The Use of Politeness Strategy and The Influence Factors in Political Talk Show - Haryanto, Haryanto; Indriani, Novita; Safar, Muh.; Fansiska, Fini Widya; Dewi, Dyah Utami (Surakarta English and Literature Journal, 2024)
Maintaining etiquette in speech acts is a part of politeness strategies conducted in communication. This study aimed to describe the use of politeness strategies and the influence factors found in the political talk show of Mata Najwa. The research method employed a descriptive qualitative one as proposed by Brown and Levinson’s four politeness strategies. Face is indicated as an inherently political element in the theory of Goffman. The data is a dialogue transcription taken from Mata Najwa YouTube.on 18 October 2023. The techniques of collecting data were documentation by watching, listening, transcribing, reviewing the transcription, and selecting the speakers’ utterances. The data analysis involved identifying, and classifying utterances based on politeness strategies, analyzing frequency, interpreting the data, and drawing conclusions. The analysis of 193 utterances showed that 114 of them had positive politeness strategy data (59%), 34 had bald-on politeness strategy data (17,6%), 24 had negative politeness strategy data (12,4%), and 21 had off-record politeness strategy data (17,6%). The positive politeness method is the most commonly employed tactic. It suggests that the inclination toward familiarity between speakers and listeners as well as the sentiment to reveal people's individuality by lowering FTA in each phrase is generated by particular factors. That becomes a point for speakers to build and maintain relationships.